Analysis of semi-active suspension systems for four-axles off-road vehicle using half model - Faris, Waleed Fekry; BenLahcene, Zohir; Ihsan, Sany Izan (Inderscience Publishers, 2009)
Handling and ride quality are affected by many factors, including high-frequency vibrations, body booming, body roll and pitch motion, vertical motion by the suspension system and frequency vibration transmitted from the road input excitations. This article focuses on the most significant vibration source that affects handling and ride quality, which is the suspension system. Passive suspension has been taken as the starting point of this work, in which we discuss the model in context. Semi-active suspension systems are introduced with the aim of exploring the performance of the system compared with passive suspension. Several control policies of semi-active systems, namely, skyhook, ground-hook and hybrid controls, are presented. Their ride comfort, suspension displacement and roadholding performances are analysed and compared with passive systems. The analysis covers both transient and steady-state responses in the time domain and transmissibility response in the frequency domain. The results show that the hybrid control policy yields better comfort than a passive suspension, without reducing the road-holding quality or increasing the suspension displacement for a typical off-road vehicle. The hybrid control policy is also shown to provide a better compromise between comfort, road-holding and suspension displacement than the skyhook and ground-hook control policies.